Sanksi Pidana Tentang Pengelolaan Sampah di Kota Jambi: Perspektif Hukum Islam: Criminal Sanctions on Waste Management in Jambi City: an Islamic Law Perspective - Tessya Yunita Siregar; Fuad Rahman; Siti Marlina (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
This research aims to determine the implementation of Regional Regulation No. 5 of 2020 concerning waste management in the City of Jambi from an Islamic legal perspective. This research uses a qualitative method that employs an empirical juridical approach. The study was conducted at the Environmental Agency of the City of Jambi, the City Police Unit (Satpol PP) of Jambi, several temporary waste disposal sites (TPS), and the final waste disposal site in Talang Gulo. The data collection methods include observation, interviews, and documentation. The results of this research reveal that the implementation of local regulations on waste management in the city of Jambi has several supporting indicators. Firstly, it includes the enforcement of the implementation of local regulations. Secondly, the socialization regarding the formation and guidance on waste management. Thirdly, the enforcement of laws related to waste management. The implementation of Regional Regulation No. 5 of 2020 concerning waste management from the perspective of Islamic criminal law in environmental management is based on the teachings of the Qur'an, hadith, and the principles of maqashid shari'ah (the objectives of Shari'ah). The principles include tauhid (faith in Allah), khalifah (leadership on earth), lā ḍarar wa lā ḍirār (there must be no harm and no harming), hifẓ al-bī‘ah (environmental protection as part of maqāṣid al-Sharī‘ah), and ta’zir (administrative and criminal sanctions in Islam).